Rezeki dalam Perspektif Al-Qur'an: Sebuah Kajian Tafsir Tematik - Bunyamin Yusuf Surur (Lajnah Pentashihan Mushaf Al-Qur'an, 2008)
This writing elaborates three parts of study. The first concerning the essence of livelihood, which studies the meaning of livelihood, as well as other terms having the similar meanings with livelihood such as an-ni'mah, al-mata', al-fadl, al-mal, al-khair, ar-rahmah, al-ala', al-kanz and al-qintar. The second is concerning the sources of livelihood, studying the livelihood from the sources of the universe such as from the earth, the sky, the ocean, the flora, and the fauna. The third is concerning the strategy to get the livelihood, the obligation to do the utmost effort, the encouragement to work hard, the understanding that not all the will can be achieved and the encouragement not to desperate when all the efforts done have not got satisfied result yet.